2020
DOI: 10.1002/jbmr.4270
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in Differentiating Osteoclast Precursors Demonstrates Enhanced Inflammatory Pathway Activation in Female Cells

Abstract: Sexual dimorphism of the skeleton is well documented. At maturity, the male skeleton is typically larger and has a higher bone density than the female skeleton. However, the underlying mechanisms for these differences are not completely understood. In this study, we examined sexual dimorphism in the formation of osteoclasts between cells from female and male mice. We found that the number of osteoclasts in bones was greater in females. Similarly, in vitro osteoclast differentiation was accelerated in female os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 57 publications
2
18
1
Order By: Relevance
“…These discrepancies probably reflect significant differences in the culture assays that were employed or the origins of the cells. Significantly, our results correlate with measurements of the number of osteoclasts in the bones of mice [14]. However, more work is clearly needed to better understand the reasons for the discrepancies between female and male cultures in the various assays.…”
Section: Osteoclast Sexual Dimorphismsupporting
confidence: 73%
See 2 more Smart Citations
“…These discrepancies probably reflect significant differences in the culture assays that were employed or the origins of the cells. Significantly, our results correlate with measurements of the number of osteoclasts in the bones of mice [14]. However, more work is clearly needed to better understand the reasons for the discrepancies between female and male cultures in the various assays.…”
Section: Osteoclast Sexual Dimorphismsupporting
confidence: 73%
“…MKP-1 is an important negative regulator of the MAPK pathways of the innate immune system [36]. In contrast to these models of inflammatory osteolysis, we found that in mice in homeostasis bone marrow-derived osteoclastogenesis was greater in cells from female than from males [14]. Hence, the model in which osteoclast sexual dimorphism is examined seems to influence what outcome is observed.…”
Section: Inflammationmentioning
confidence: 57%
See 1 more Smart Citation
“…So that an increase in the BV of Notch2 tm1.1Ecan would not necessarily represent a rescue of the osteopenic phenotype and that HES1 was a mediator of NOTCH2. It is not readily apparent why the Hes1 inactivation caused a phenotype in female but not in male mice, and the observation stresses the importance of examining phenotypes in mice of different sexes independently ( 56 , 57 ). It is not unusual to observe sex-specific phenotypes in genetically engineered mice ( 58 , 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is not unusual to observe sex-specific phenotypes in genetically engineered mice ( 58 , 59 , 60 ). Possible explanations for the prevalence of a phenotype in female mice include genetic influences, a loss of the inhibitory actions of estrogens on osteoclastogenesis in the context of the Hes1 inactivation as well as the earlier NF-κB–NFATc1 activation and osteoclastogenesis that occurs in female mice ( 57 , 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%